The Effect of Adaptive Leadership on Employee Performance and Organizational Sustainability - Latifah, Mufadlolul (Economic and Business Horizon, 2024)
In the era of Volatility, Uncertainty, Complexity, and Ambiguity (VUCA), adaptive and innovative leadership is a key factor in improving employee performance and maintaining organizational sustainability. This study aims to identify effective leadership styles in influencing employee performance as well as explore the intermediary variables that contribute to these relationships. The research method used is a quantitative approach with survey techniques to collect data from various organizations. The results show that effective leadership not only plays a role in providing direction, but also in creating a supportive and motivating work environment for employees. Additionally, factors such as organizational culture, company policies, and individual motivation have an influence on employee productivity and loyalty. Furthermore, the study found that leadership that supports organizational sustainability is able to create more effective long-term strategies. Therefore, organizations need to implement a leadership strategy that is not only oriented towards achieving targets, but also on developing human resources and creating a healthier and more innovative work environment.